Do we need more natural gas in New England? Evidence from demand estimation - Peng, Shenghao. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Economics.; Advisor: Gilbert Metcalf.; Committee: Gilbert Metcalf, and Ujjayant Chakravorty.; Keyword: Economics.